Generation of a fluorescent hESC reporter line (Kle033-A-1) for the isolation of distinct midbrain progenitor cell types - Emilía Sif Ásgrímsdóttir; Ernest Arenas (Stem Cell Research)
Midbrain dopaminergic (mDA) neurons derived from human pluripotent stem cells (hPSCs) offer a promising cell source for cell replacement therapy in Parkinson’s disease (PD). Single-cell RNA sequencing (scRNA-seq) of the developing human ventral midbrain has identified four cell types expressing markers used to define correctly patterned mDA progenitors. Here, we use CRISPR/Cas9 to generate a fluorescent human embryonic stem cell line for the isolation of two potential mDA progenitors, Rgl1 and ProgM. We expect that by isolating specific mDA progenitor cell type/s and defining their function, it may be possible to develop more precise cell replacement strategies for PD.